Exploring the impact of a brief mindfulness induction on motor inhibitory control. (3rd August 2020) - Aminoff, Elissa; Jaiswal, Satish; Tsai, Shao-Yang; Juan, Chi-Hung; Liang, Wei-Kuang; Muggleton, Neil G.
Abstract: Inhibitory control can be divided into motor and cognitive inhibition. The current research is the first study exploring the impact of brief mindfulness training on motor inhibition, measured by a stop signal task in participants without any meditation experience. Motor inhibition performance was compared before and immediately after three different conditions; a brief mindfulness induction, a resting state and an active control session in which participants listened to their favorite music. Post-test learning effect on go-reaction times was seen for the resting and mindfulness conditions, but was absent in the music session, possibly due to emotional arousal might have led slower responses. Brief mindfulness training did not significantly alter inhibitory control, although marginal improvement in stop signal reaction time following the mindfulness induction was observed. Motor inhibition appears unresponsive to either short-term or long-term mindfulness practice. Future mindfulness studies should explore a broad spectrum of cognitive functions and populations.